2010
DOI: 10.1007/s11745-010-3515-z
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Training in Rats Increases Skeletal Muscle Sphingomyelinase and Serine Palmitoyltransferase Activity, While Decreasing Ceramidase Activity

Abstract: Sphingolipids are important components of cell membranes that may also serve as cell signaling molecules; ceramide plays a central role in sphingolipid metabolism. The aim of this study was to examine the effect of 5 weeks of aerobic training on key enzymes and intermediates of ceramide metabolism in skeletal muscles. The experiments were carried out on rats divided into two groups: (1) sedentary and (2) trained for 5 weeks (on a treadmill). The activity of serine palmitoyltransferase (SPT), neutral and acid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 46 publications
3
22
0
Order By: Relevance
“…Chronic endurance training decreases muscle ceramide content in rodents [41] and humans [10][11][12] [42]. Additionally, endurance training decreased the C18:0 sphingomyelin content of human muscle, which may help explain the lower C18:0 ceramide levels in athletes in this study [14].…”
Section: Discussionmentioning
confidence: 66%
“…Chronic endurance training decreases muscle ceramide content in rodents [41] and humans [10][11][12] [42]. Additionally, endurance training decreased the C18:0 sphingomyelin content of human muscle, which may help explain the lower C18:0 ceramide levels in athletes in this study [14].…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, the involvement of ceramide-derived sphingosines in the activation of AMP-activated protein kinase by adiponectin, downstream from the adiponectin receptors, was recently suggested [67]. This mechanism, which should operate in the muscle, suggests a new role for the sphingolipid metabolism [66] with respect to its long-disputed role in affecting muscle insulin sensitivity [65], [66], [68][70]. Our results further support the importance of SM(OH) C24∶1 as a marker of the muscle sphingosines metabolism.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, it has been shown that key enzymes of ceramide metabolism in rat muscles are modulated in response to physical activity. This is accompanied by an increased insulin sensitivity, suggesting a crucial role of sphingolipids in skeletal glucose homeostasis [35].…”
Section: Discussionmentioning
confidence: 99%